HUBUNGAN KEMANDIRIAN BELAJAR DAN MOTIVASI BERPRESTASI DENGAN HASIL BELAJAR MATA PELAJARAN EKONOMI SISWA KELAS XI SMAN 01 BELIMBING - Arni Salmah; Dessy Triana Relita; Yulia Suriyanti (STKIP Persada Khatulistiwa Sintang, 2020)
Abstract: The goodIndependence of learning and motivation support the successful implementation of learning activities. Based on the data, was found that most of the students learning outcomes very good, was influenced by high level of learning independence and student motivation. The formulation of the problem in this study is whether there is a relationship of learning independence and achievement motivation with the learning outcomes of economic subjects of class XI students of SMA Negeri 01 Belimbing in the Academic Year 2019/2020. The purpose of this study was to determine the relationship of learning independence and achievement motivation with learning outcomes in economic subjects for class XI students of SMA Negeri 01 Belimbing in the 2019/2020 Academic Year. Research results 1) There is a relationship between independence and student learning outcomes of 0.440 with a sufficient level of relationship. 2) There is a relationship between achievement motivation with student learning outcomes of 0.630 with a strong relationship level. 3) There is a significant relationship between learning independence and achievement motivation with student learning outcomes in XI IPS class of SMA Negeri I Belimbing in the 2019/2020 Academic Year. Keywords: Independence of learning, Achievement Motivation, Learning Outcomes Abstrak: Kemandirian belajar dan motivasi berprestasiyang baik mendukung keberhasilan pelaksanaan kegiatan pembelajaran.Berdasarkan data nilai ulangan harian ditemukan bahwa sebagian besar nilai siswa sangat baik, hal ini dipengaruhi oleh faktor tingginya kemandirian belajar dan motivasi berprestasi siswa. Rumusan masalah dalam penelitian ini adalah apakah terdapat hubungan kemandirian belajar dan motivasi berprestasi dengan hasil belajar mata pelajaran ekonomi siswa kelas XI SMA Negeri 01 Belimbing Tahun Pelajaran 2019/2020. Tujuan penelitian ini adalah untuk mengetahui hubungankemandirian belajar dan motivasi berprestasi dengan hasil belajar mata pelajaran ekonomi siswa kelas XI SMA Negeri 01 Belimbing Tahun Pelajaran 2019/2020. Hasil penelitian 1) Terdapat hubungan antara kemandirian dan hasil belajar siswa sebesar 0,440 dengan tingkat hubungan yang cukup. 2) Terdapat hubungan antara motivasi berprestasi dengan hasil belajar siswa sebesar 0,630 dengan tingkat hubungan yang kuat. 3) Terdapat hubungan yang signifikan antara kemandirian belajar dan motivasi berprestasi dengan hasil belajar siswa di kelas XI IPS SMA Negeri I Belimbing Tahun Pelajaran 2019/2020. Kata kunci: Kemandirian Belajar, Motivasi Berprestasi, Hasil Belajar